Teknologi Sistem Peringatan Dini Berbasis Programmable Logic Controller Dalam Upaya Mengantisipasi Bencana Banjir Di Kecamatan Mempawah Hilir Kabupaten Pontianak - Harjono, Purwo; Hayati, Nur; Panjaitan, Seno D. (Faculty of Engineering, Universitas Tanjungpura, 2009)
Abstract This research is indicate that the ability of early warning system technology in giving information early related to floods quickly and nowadays especially in watching condition of rainfall and ebb intensively. Therefore require to be designed by appliance which can give the early information to society in region of gristle of floods disaster to conduct actions which require to be drawn up by before the happening of disaster. Location of floods gristle selected by countryside of sand the mempawah subdistrict go downstream the forewarning system designed use the programmable logic controller (PLC) and system can give result of information in the form of forewarning indicator which is depend on storey, water height level, that is normal level, attentive level, alert level and caution level. Water height level can be watched from face door irrigate as one of appliance to support the system of forewarning floods disaster. Design result to develop, build this appliance is very be of benefit to society in doing early anticipation possible the happening of floods disaster, so that loss generated by effect of floods disaster felt by society during the time earn the minimum. The existence of forewarning appliance is threatened society of danger can act during which is last for lessening possibility of the happening of hurt victim, loss of soul, and destroy the good and chattel. Keywords Early, warning, system, floods, disaster.